2015
DOI: 10.4314/ijbcs.v9i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the standing vegetation, soil properties and soil seed bank of an industrially degraded vegetation of Iron Smelting Factory

Abstract: This study assessed the floristic composition, soil properties and the soil seedbank of the vegetation around the Iron smelting factory. This was with a view to determining the functional role played by soil chemical composition and the seed bank in the modifications of vegetation patterns. Five 100 m × 5 m plots were selected from the study site; vegetation, soil seed bank and some soil chemical parameters were assessed. One-way Analysis of Variance and Duncan multiple range tests were employed for data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The composition of seed bank may reflect the richness of species present in a particular vegetation and its surroundings (Cabin et al, 2000). Similar to the previous findings (Akinyemi and Oke 2013;Olatunji et al, 2015), the present study revealed that in all the physiognomies, seeds from herbaceous plants were the earliest seedling to emerge from the seed bank. This indicated that like many other ecosystems, the seeds of herbaceous species at Ibodi monkey forest have short periods of dormancy and therefore their seeds were the first set of seeds to meet suitable conditions for germination.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The composition of seed bank may reflect the richness of species present in a particular vegetation and its surroundings (Cabin et al, 2000). Similar to the previous findings (Akinyemi and Oke 2013;Olatunji et al, 2015), the present study revealed that in all the physiognomies, seeds from herbaceous plants were the earliest seedling to emerge from the seed bank. This indicated that like many other ecosystems, the seeds of herbaceous species at Ibodi monkey forest have short periods of dormancy and therefore their seeds were the first set of seeds to meet suitable conditions for germination.…”
Section: Discussionsupporting
confidence: 90%
“…This indicated that like many other ecosystems, the seeds of herbaceous species at Ibodi monkey forest have short periods of dormancy and therefore their seeds were the first set of seeds to meet suitable conditions for germination. Olatunji et al (2015) reported that herbaceous species such as Chromolaena odorata and Euphorbia heterophylla were the first set of seedlings recorded in the first week of seedling emergence test from soil samples taken from a tropical rainforest in Nigeria. In addition, the observed differences in dominant characteristic of herbaceous species among the physiognomies may be attributed to the varying degree of canopy openings which enhances the dispersal of seeds of these herbaceous species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher diversity, in less-disturbed vegetation, is determined by niche variability and therefore the variability of biotic and abiotic factors favorable to the development of several species (Tiokeng et al, 2015). Among the abiotic factors, soil properties affected the establishment of tree species (Olatunji et al, 2015), and it may be the case due to the vertisols (black-cotton ill drained soil) in Lama forest. In SF, our results support those of Makana and Thomas (2006) who also observed good recovery of the diversity of SF in Ituri (Democratic Republic of Congo) because of edge effects, relatively low diversity of the primary forests, and the age since abandonment.…”
Section: Comparison Of Structural Attributes According To Forest Stagmentioning
confidence: 99%